State-estimation for a class of tubular reactors using a pointwise innovation scheme. (December 2017) - Schaum, A.; Alvarez, J.; Meurer, T.; Moreno, J.A.
Highlights: The point-wise innovation scheme is applied for a class of exothermic tubular reactors. A simple and numerically efficient estimation scheme is obtained. A criterion for sensor location is provided. Convergence conditions are established in terms of sensor locations and reactor parameters. The estimator is put into perspective with the extended Kalman filter. Abstract: The problem of estimating the spatio-temporal temperature and concentration distribution in a tubular reactor with first order exothermic reaction and in-domain pointwise temperature measurements is considered. The problem is addressed using a simple pointwise innovation (PWI) structure, which imposes the measurement information at the sensor location in the simulator. Rigorous convergence conditions are presented in terms of the sensor location and reactor parameters. The approach is tested in numerical simulation studies and put in perspective with the (continuous time) extended Kalman filter (EKF) for a benchmark reactor with up to five steady-state profiles. In the simulations the proposed PWI scheme shows a good convergence behavior even in the presence of large initial errors, unmeasured feed perturbations, measurement noise and parameter mismatch.